2018
DOI: 10.1097/iae.0000000000001538
|View full text |Cite
|
Sign up to set email alerts
|

Royal College of Ophthalmologists' National Database Study of Vitreoretinal Surgery

Abstract: PRECISA database study of 5,857 primary retinal detachment operations found no difference in failure rate between surgeon grades. 1,3 , David Yorston FRCOphth 3,4 , David HW Steel FRCOphth 3,5,6 , Tom H Williamson MD FRCOphth 3,7 , Timothy L Jackson PhD, FRCOphth 8 , John M Sparrow DPhil FRCOphth 3,9 The RD re-operation rate at 6 months after primary surgery was 13.9% (725/5,202), and did not differ significantly between consultants and trainees (p = 0.382). For surgeons contributing ≥50 cases, the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…(13)(14)(15)(16) Re-detachment rate after primary vitrectomy for RRD may be variable according to several authors but it is estimated to be between 10 and 20% in most of the published series. (12,15,(17)(18)(19) Lens status could be a differential prognostic factor for failure according to Caiado et al, who found a much higher rate of re-detachment after primary vitrectomy for RRD in phakic compared to pseudophakic eyes. (20) In our series, we also found a slight tendency towards a worse PSR in the phakic compared to pseudophakic arm (10.5% versus 7.1%); however, it was not statistically significant (p=0.42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(13)(14)(15)(16) Re-detachment rate after primary vitrectomy for RRD may be variable according to several authors but it is estimated to be between 10 and 20% in most of the published series. (12,15,(17)(18)(19) Lens status could be a differential prognostic factor for failure according to Caiado et al, who found a much higher rate of re-detachment after primary vitrectomy for RRD in phakic compared to pseudophakic eyes. (20) In our series, we also found a slight tendency towards a worse PSR in the phakic compared to pseudophakic arm (10.5% versus 7.1%); however, it was not statistically significant (p=0.42).…”
Section: Discussionmentioning
confidence: 99%
“…For RRDs treated by primary vitrectomy, PSR is reported to range between 80 and 90% in most published series. (9)(10)(11)(12) Despite being vitrectomy the prevalent treatment approach for the disease, several issues are still under debate, such as the usefulness of adding an encircling band, especially in cases with inferior breaks, the type of tamponade that is better in each case, and the potential benefit of 360 degrees peripheral laser photocoagulation in the first surgery.…”
Section: Introductionmentioning
confidence: 99%